RAINFALL VARIATIONS ALONG THE TEESTA VALLEY IN MOUNTAINOUS SLOPE OF SIKKIM (MAUSAM, 1994)
The mean weekly rainfall and iu rate oCchanee al Tadona and Ga~t. h ave been analysed toHJ: d ates of onset and withdrawal of southwest monsoon. The study attem pts to anal)'IC broad upecU oC raWaiVprecipitation di etributicn during th e four seaso ns. Th e importance oCorogra phy (or the rainfall in the mountainoUsvalley ha s been brought out. Th e study is based on da ta of 12 stations and of va ryina period of 4-25 yean.RainfaU over this mount ainous slope is found mono-modal with 8 maximum in Jul,...Aueult. Rainfall in thevalley shows sirikina: dilference in pa tterns even aLsho rt distance (4 km) and situated at a bieber altitude. Ra infallO~T station s in the valley increased up to 2000m esl and then decrease sharply. The central part ofthe valley with anaverage altitude of ISOQ.2000 m asl receives about 2~300 em of rainfall durina aouthwest monsoon season